The manurial effect of Cape Barren Goose droppings - Marriott, Richard W (Wildfowl, 1973)
Fresh droppings from Cape Barren Geese Cereopsis novaehollandiae applied to grass produced an increase in the weight of grass cropped after 4 months. No ’burning’ effect on the grass was observed.